ON THE RELATION OF CHRONIC INTERSTITIAL PANCREATITIS TO THE ISLANDS OF LANGERHANS AND TO DIABETES MELUTUS - Opie, Eugene L. (The Rockefeller University Press, 1901)
(1) Congenital syphilitic pancreatitis retards the development of the glandular acini but does not affect the islands of Langerhans. Embedded in the stroma, but not invaded by it, the latter maintain their continuity with the small ducts and acini with which they have a common origin. (2) Two types of chronic interstitial inflammation affecting the developed pancreas are distinguishable: (a) Interlobular Pancreatitis.—In the interlobular variety the inflammatory process is localized chiefly at the periphery of the lobule and implicates the islands of Langerhans only when the sclerotic process has reached a very advanced grade. When pancreatitis has followed obstruction of the ducts, the islands long remain unaltered though embedded in dense scar-like tissue. (b) Interacinar Pancreatitis.—In the interacinar type the process is diffuse, invading the lobules and separating individual acini. The inflammatory change invades the islands of Langerhans. (3) A relationship has been observed between lesions of the islands of Langerhans and the occurrence of diabetes mellitus. (a) In one of eleven cases of interlobular panereatitis diabetes of mild intensity occurred. The sclerosis, which in this case followed obstruction of the ducts by calculi, was far advanced and affected the islands of Langerhans. (b) In two of three cases of interacinar pancreatitis, diabetes was present. The third case was associated with a condition, hæmochromatosis, which at a later stage is associated with diabetes, the result of pancreatic lesion. (c) In a fourth case of diabetes, hyaline deposit between the capillaries and the parenchymatous cells had so completely altered the islands of Langerhans that they were no longer recognizable.